Economic relations between personal and corporate income tax - Tomasz Skica; Tomasz Wołowiec; Pavel Pavlov (e-Finanse: Financial Internet Quarterly, 2014)
The main goal of this article is to discuss the mutual economic relations between personal and corporate income taxes. The article consists of three parts. The first is an introduction to these taxes and taxation. The second is the analysis in which the objective of the taxation is discussed. This part represents the trends in research on taxation and clarifies the aspects of taxes that should be considered in an optimal tax system construction. These include solutions which stimulate taxpayer behavior, the economically and socially oriented objectives of taxation, and guides needed for tax equalization. The conclusions are focused on the tax rates in personal and corporate income tax and their influence on economic behavior of firms and individuals. The authors show different points of view on tax rate equalization and discuss its consequences.
Keywords: H21; H24; H30; E62; 330; personal income tax; corporate income tax; fiscal stimulus; budgetary system; fiscal policy